Physical characteristics of novel nanomagnetic radiopharmaceuticals: a review - Aysa, Noor Hadi; Aziz, Safa Wahab; Saleh, Rasha Hadi; Hamza, Lena Fadhil; Al-Assaly, Rafal (Pharmakeftiki, 2025)
Hybrid nanomagnetic radiopharmaceuticals represent a frontier in targeted therapy and diagnostic imaging. These compounds synergistically combine magnetic nanoparticles with radiopharmaceutical agents in order to enhance the precision, delivery, and therapeutic efficacy of nuclear medicine interventions. This review summarizes their physicochemical properties, presents their mechanisms of action, and discusses their translational potential across a range of clinical applications.